A Cross-Sectional Study of the Relationship between Previous Military Experience and Mental Health Disorders in Currently Serving Public Safety Personnel in Canada. (May 2020) - Groll, Dianne L.; Ricciardelli, Rosemary; Carleton, R. Nicholas; Anderson, Greg; Cramm, Heidi
Objective: There is an increased incidence of some mental health disorders such as post-traumatic stress disorder (PTSD) in some members of the military and in some public safety personnel (PSP) such as firefighters, police officers, paramedics, and dispatchers. Upon retirement from the armed forces, many individuals go on to second careers as PSP. Individuals with prior military experience may be at even greater risk than nonveterans for developing mental health disorders. The present study was designed to examine the relationship between prior military service and symptoms of mental health disorders in PSP. Methods: This is a cross-sectional, observational study. Data for this study were collected from an anonymous, web-based, self-report survey of PSP in Canada. Invitations to participate were sent to PSP via their professional organizations. Indications of mental disorder(s) and symptom severity were assessed using well-validated self-report screening measures. Results: Of the survey respondents who provided this information, 631 (6.8%) had prior armed forces experience; however, not all responses were complete. Ex-military PSP reported significantly more exposure to traumatic events and were approximately 1.5 times more likely to screen positive for indications of PTSD, mood, anxiety, or acute stress disorders and to have contemplated suicide than those without prior armed forces experience. Conclusions: In our study, individuals in PSP with prior service experience in the armed forces were more likely to screen positive for indicators of some mental health disorders. Accordingly, mental health practitioners should inquire about previous service in the armed forces when screening, assessing, and treating PSP.